PENGARUH VARIASI JUMLAH PLAT ELEKTRODA PADA ELEKTROLIZER TERHADAP VOLUME DAN LAJU PRODUKSI GAS HHO (HIDROGEN-HIDROGEN-OKSIGEN) - Arianto, Rian; Martias, Martias; Sugiarto, Toto (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Energy is the initial driving source in the automotive field. Where in the automotive world there is renewable energy such as hydrogen gas. Hydrogen gas is a gas-shaped fuel that has the characteristics of colorless, tasteless, and odorless. Hydrogen gas can be produced by electrolysis of water (H2O). Where the electrolyte solution will be reacted using an electric current to produce hydrogen (H2) gas and oxygen gas (O). This study uses experimental research methods to determine the effect of variations in the number of electrode plates on the electrolizer on the volume and rate of HHO gas production using a measuring cup. The results showed that the effect of the variation in the number of electrode plates on the electrolyzer to the highest HHO gas volume occurred in the variation of 14 electrode plates with an increase of 33%. While for the highest gas production rate occurs in the variation of 14 electrode plates with an increase of 36%.